DNase-targeted natural product screening based on a sensitive and selective DNase I detecting system. Issue 49 (15th June 2017) - Zhao, Chuan; Chen, Yanjiao; Fang, Jun; Fan, Jialong; Tong, Chunyi; Liu, Xuanming; Liu, Bin; Wang, Wei
Abstract : As a widely used deoxyribonuclease, DNase I is involved in many physiological processes including tumor cell proliferation, metastasis and apoptosis. Abstract : As a widely used deoxyribonuclease, DNase I is involved in many physiological processes including tumor cell proliferation, metastasis and apoptosis. Furthermore, the level of this enzyme in serum can act as a functional biomarker for the therapeutic monitoring of systemic lupus erythematosus and other diseases. We report here a low cost and sensitive DNase I detecting system based on the single-stranded fluorogenic substrate and nanographene oxide (NGO) and use it for DNase-targeted natural product screening. The system with a detection limit of 0.005 U was then used to evaluate the effect of external factors on DNase I. The results show that Hg 2+, As 2+, Pb 2+, Cd 2+ and Cu 2+ can inhibit DNase I activity in a concentration-dependent manner with IC50 values of 0.37 mM (Hg 2+ ), 2.7 mM (As 2+ ), 5 mM (Pb 2+ ), 5.3 mM (Cd 2+ ) and 7.8 mM (Cu 2+ ), respectively. Meanwhile, 10 natural compounds isolated from Cyclocarya paliurus leaves were screened as DNase I inhibitors, while 5 compounds were identified as activators. Finally, the system was used to discriminate DNase activity of serum samples with and without HBV. The results showed that HBV infection significantly decreased the level of DNase I in serum samples. In summary, these data indicate that this method with the advantages of rapidity, low cost and high sensitivity is hopeful for DNase assay in biological samples as well as compound screening in vitro .